2016
DOI: 10.1097/sih.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study Assessing Healthcare Provider’s Knowledge of Pre-Eclampsia and Eclampsia in a Tertiary Referral Center

Abstract: Our results show widespread magnesium sulfate utilization; however, the use of antihypertensive medication is not universally administered in compliance with current guidelines. The importance of blood pressure management to reduce maternal morbidity and mortality in the setting of pre-eclampsia needs to be emphasized. Interestingly, availability of a cognitive aid did not ensure its utilization in this scenario. Findings suggest that for cognitive aids to be effectively used, it is essential that staff has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
6
0
2
Order By: Relevance
“…The study was conducted in accordance with the Declaration of Helsinki, and the protocol was approved by the Ethics Committee of Ärztekammer Westfalen-Lippe (2014-657-f-N) that waived the obligation to obtain consent. The study is registered at the German Clinical Trial Registry (DRKS00022132) and reported herein according to the extensions to the CONSORT statements of the Reporting Guidelines for Health Care Simulation Research [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted in accordance with the Declaration of Helsinki, and the protocol was approved by the Ethics Committee of Ärztekammer Westfalen-Lippe (2014-657-f-N) that waived the obligation to obtain consent. The study is registered at the German Clinical Trial Registry (DRKS00022132) and reported herein according to the extensions to the CONSORT statements of the Reporting Guidelines for Health Care Simulation Research [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was noted that no prior training for their use had been provided to participants (and the correct checklist was only used in 75% of cases). is and other studies highlight the need to adequately train professionals to make CAs an effective tool as part of the implementation strategy [21,22]. In our study, the training tool for CAs use was simulation in the majority of cases in France although this was less often the case in Canada.…”
Section: Discussionmentioning
confidence: 64%
“…Ainda constatou-se haver um certo sentimento de hierarquização entre médico e enfermeiro. A limitação de recursos humanos associada à falta de suprimentos também é um agravante na prestação de qualidade dos serviços, uma vez que, há uma sobrecarga de trabalho que os impede de fazer uma avaliação minuciosa para se obter um diagnóstico e tratamento precoces (17) .…”
Section: Evidenciou Uma Dificuldade Dosunclassified